TUBUH SOSIAL SEBAGAI MODAL SIMBOLIK DI SEKTOR KERJA FORMAL KOTA DENPASAR - Mujiatno, Fidiana Rakmawati; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This research attempts to explain how significant the role of the social body for job seekers in Denpasar City. The social body is meant here is an attractive appearance, beauty or good looking, as well as the proportional body for job seekers. This study used a qualitative approach and was analyzed by using social body theory from Marry Douglas. Being attractive itself goes into the aspect of symbolic capital that must be owned by someone in order to compete in the world of work. This competition arises not only during the selection process of new employee acceptance but also when the workers have entered into a company or agency where they work, considering the social body present in the capitalist system makes the symbolic capital possessed by a person exchanged as an exchange value. Therefore, a worker in some company could earn a bonus in salary which will be received each month if the worker is able to perform an attractive appearance in their work workplace. Keywords: Formal Working Sector, Social Body, Symbolic Capital.